Hugless friends and heroic mice. - Craig, Amanda (New Statesman, 2020)
The Critics: Books Coronavirus has touched everything, and children's literature reflects this sooner than other forms. Alternatively, Michelle Robinson's Do Not Disturb the Dragons (Bloomsbury, £5.99, 6-8) is an illustrated comic caper about two intrepid girls training to be knights in a castle where dragons nest. We can do anything", Lotti says, and Farrant pushes her steely prose and thrilling narrative with all the resolution of the barge that carries them across the sea.